Language Discrepancy and Separation of East Pakistan 1971 - Hanif , Kalsoom (South Asian Journal of Social Sciences and Humanities, 2021)
The separation of the East Pakistan in 1971 is considered a dark phase in Pakistan’s history. This article analyzes the fact that along with geographical, economic and political factors one of the most important causes was language discrepancy. The areas which Pakistan acquired at the time of partition were inhabited by people of different races who used to speak different languages for example Urdu, Balochi, Sindhi, Punjabi and Bengali. Despite of the fact that Bengali was mother tongue of the 57 percent of the population, Jinnah declared Urdu the official language of Pakistan. The claim of the Government was that Bengali language as official language means accepting demands of Hindus and communist elements and some discontented elements of Muslim League. The movement for making Bengali the official language started in 1947 throughout East Pakistan. This research study therefore will focus the language issue which led to certain movements. The paper examines that first lingual feelings generated, and later economic grievances developed which nurtured the Bengali separatist movement. Therefore, main research question of the paper is how language issue helped Bengali people to sharpen their national identity.